Turbogenerator Steam Turbine Variation in Developed Power: Analysis of Exergy Efficiency and Exergy Destruction Change. (2nd July 2018) - Mrzljak, Vedran; Senčić, Tomislav; Žarković, Božica
Abstract : Developed power variation of turbogenerator (TG) steam turbine, which operates at the conventional LNG carrier, allows insight into the change in turbine exergy efficiency and exergy destruction during the increase in turbine power. Measurements of required operating parameters were performed in eight different TG steam turbine operating points during exploitation. Turbine exergy efficiency increases from turbine power of 500 kW up to 2700 kW, and maximum exergy efficiency was obtained at 70.13% of maximum turbine developed power (at 2700 kW) in each operating point. From turbine developed power of 2700 kW until the maximum power of 3850 kW, exergy efficiency decreases. Obtained change in TG turbine exergy efficiency is caused by an uneven intensity of increase in turbine developed power and steam mass flow through the turbine. TG steam turbine exergy destruction change is directly proportional to turbine load and to steam mass flow through the turbine—higher steam mass flow results in a higher turbine load which leads to the higher exergy destruction and vice versa. The higher share of turbine developed power and the lower share of turbine exergy destruction in the TG turbine exergy power inlet lead to higher turbine exergy efficiencies. At each observed operating point, turbine exergy efficiency in exploitation is lower when compared to the maximum obtained one for 8.39% to 12.03%.